Dix petits hacks Tinder : les algorithmes au service d’une économie spéculative des rencontres amoureuses et sexuelles - David MYLES; Martin BLAIS (Tic & Société)
The mediation of love and sexuality has often relied on dating advice. This paper analyses a corpus of dating guides concerning the popular app Tinder. Our analysis suggests that the practice of algorithmic blackboxing, that is, characterizing algorithms as black boxes, is central to these guides that rely on the alleged opacity of Tinder’s algorithms to praise certain products, advice, or services that aim to facilitate matchmaking. The practice of algorithmic blackboxing primarily encourages users to hack Tinder. In this context, the notion of hack stresses the importance for users to modulate their behaviours in ways that make them more algorithmically recognisable, especially in relation to their gender. Thus, we suggest that Tinder’s algorithms participate in reproducing a speculative dating economy.